Does watching a movie improve empathy? A cluster randomized controlled trial (Canadian Medical Education Journal, 2019)
Background: We studied if watching a movie about the patient physician encounter alone or in combination with a communication skills training workshop could improve empathy score of medical students. Methods: One hundred and thirty three medical students participated in one of the following four groups of the study. Group A: a three hour workshop (42 students); group B: watching the movie “The Doctor” (23 students); group C: watching the movie “The Doctor”, then, participating in a three hour workshop the next day (22 students); group D: control group with no intervention (46 students). Participants completed Jefferson Scale of Empathy (JSE), Student Version to assess empathy score before and after the intervention, and one month later. A linear mixed effect model analyzed the effect of intervention across groups considering the effects of other significant variables. Results: All of the three interventions had an immediate improving effect on empathy scores compared to control group. However, the improvement effect remained significant only in groups A (p=.015) and C (p=.001) one month later. Conclusions: Watching selected movies has a significant but transient effect on empathy of students. Combining two methods of watching the movie and communication skills workshop, seems to add the beneficial effects.